2016
DOI: 10.1002/cam4.746
|View full text |Cite
|
Sign up to set email alerts
|

Fascin‐1 as a novel diagnostic marker of triple‐negative breast cancer

Abstract: In some cases of breast cancer, diagnosis of triple‐negative breast cancer (TNBC) requires further fluorescence in situ hybridization (FISH) for determining human epidermal growth factor receptor 2 (HER2) status. However, few cases undergo FISH in China, leading to difficulty regarding subsequent treatment decisions. Here, we used immunohistochemical analysis to explore expression of fascin‐1, an actin‐bundling protein, as a diagnostic marker of TNBC. A total of 457 cases of breast cancer were divided into fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 17 publications
3
46
0
Order By: Relevance
“…The high frequency of KRAS or BRAF mutations confers SAC with an important resistance to current anti-epidermal growth factor receptor therapies 9,10 . Similarly, several authors have reported that fascin1 is overexpressed in triple negative/basal phenotype breast carcinoma [22][23][24] . Given the role of fascin1 in invasion and metastasis, we performed a bioinformatic search for in silico identification of chemical compounds blocking this protein.…”
Section: Discussionmentioning
confidence: 70%
“…The high frequency of KRAS or BRAF mutations confers SAC with an important resistance to current anti-epidermal growth factor receptor therapies 9,10 . Similarly, several authors have reported that fascin1 is overexpressed in triple negative/basal phenotype breast carcinoma [22][23][24] . Given the role of fascin1 in invasion and metastasis, we performed a bioinformatic search for in silico identification of chemical compounds blocking this protein.…”
Section: Discussionmentioning
confidence: 70%
“…We also enrolled 154 untreated women scheduled for breast cancer surgery at the Affiliated Dongyang Hospital of Wenzhou Medical University (Dongyang, Zhejiang, China) between 2007 and 2017; one tissue specimen was obtained from each participant. Tumor grades were assigned using the Scarff-Bloom-Richardson system and the World Health Organization breast tumor classification criteria were used for pathohistological diagnosis [23] Cases were assigned estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER2) and Ki-67 status and subtyped as Luminal A (ER-positive [+] and/or PR + , HER2-negative [-], Ki-67 <14%), Luminal B (ER + and/or PR + , HER2 -, Ki-67 ≥14%, ER + and/or PR + , HER2 + ), HER2-enriched (ER -, PR -, HER2 + ), or as triple-negative breast cancer (TNBC; ER -, PR -, HER2 -) [24,25,26]. Clinicopathological information was collected from electronic medical records and at study entry each study participant completed a standardized questionnaire providing sociodemographic data.…”
Section: Participantsmentioning
confidence: 99%
“…Previous studies have showed that both the expression of fascin-1 and laminin-5 were associated with the invasiveness and prognoses of several cancers, including colorectal (Adams, 2015;Fukazawa et al, 2015), gastric (Saito et al, 2010;Tu et al, 2016), pancreatic (Tsai et al, 2013;Chen et al, 2015) cancers and breast adenocarcinomas (D'Alfonso et al, 2015;Wang et al, 2016). Recently, some authors reported that the expression of fascin-1 and laminin-5 were associated with clinico-pathological characteristics of non-small cell lung cancer (Moriya et al, 2001;Niki et al, 2002;Pelosi et al, 2003;Choi et al, 2006;An et al, 2012;Ling et al, 2015;Luo et al, 2015;Zhao et al, 2015;Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%